Preparation and Physico Chemical Analysis of a Herbomineral Rejuvenative Formulation- Lakshmi Vilasa Rasa - Archana V; S Thara Lakshmi (International Journal of Ayurveda and Pharma Research, 2022)
Lakshmi vilasa rasa (LVR) is a Kharaliya preparation mentioned in the Visha upavishadi Vijnaneeya Taranga of Rasa Tarangini indicated for Roga durbala deha, Krsa, Dehapushti, Vahnimandya, Lavanya vardhana etc. It consists of six ingredients namely Shoditha Parada, Shoditha Gandhaka, Loha Bhasma (LB), Shoditha Kupeelu, Shoditha Tankana and Maricha triturated thrice in four Bhavana media. The current study sheds light on the methodology and results of the preparation and analytical study of Lakshmi vilasa rasa. The physico chemical analysis of LVR revealed the following- pH 8.76, Loss on drying 10.94%, Water soluble extractive 38% and Alcohol soluble extractive 0.89%. Weight variation test of Lakshmi vilasa rasa showed that the Gulikas were within the acceptable limit. Particle size analysis (PSA) of LB was 432.69nm.